2020
DOI: 10.1111/jon.12786
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Decline and White Matter Integrity Degradation in Myotonic Dystrophy Type I

Abstract: BACKGROUND AND PURPOSE Myotonic Dystrophy Type I (DM1) is a neurodegenerative, genetic, and multisystemic disorder with a large variety of symptoms due to a CTG trinucleotide expansion located on Dystrophia Myotonica Protein Kinase (DMPK) gene. Previous reports have shown cognitive deterioration in these patients. Given that white matter (WM) degradation has also been reported in DM1 patients, here we explored if alterations in the cognitive profile of DM1 patients could be related to the deterioration of WM. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…However, in the context of understanding the neurobiology of DM1 and moving toward reliable therapeutic targets, it is vital to be able to identify which symptoms are related to brain pathology and which ones are secondary to the stress of dealing with a chronic disease and not due to underlying brain pathology (15). Previous studies have shown significant relationships between neuroimaging findings and cognitive impairments, including white matter track DTI measures, ventricular enlargement, gray matter and white matter atrophy, white matter lesions, increased hippocampal volume, and FDG-PET frontotemporal hypometabolism (4,9,12,19,(66)(67)(68). Previous studies have also confirmed cognitive decline over time with age and a negative association with disease duration (49,50,69,70).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the context of understanding the neurobiology of DM1 and moving toward reliable therapeutic targets, it is vital to be able to identify which symptoms are related to brain pathology and which ones are secondary to the stress of dealing with a chronic disease and not due to underlying brain pathology (15). Previous studies have shown significant relationships between neuroimaging findings and cognitive impairments, including white matter track DTI measures, ventricular enlargement, gray matter and white matter atrophy, white matter lesions, increased hippocampal volume, and FDG-PET frontotemporal hypometabolism (4,9,12,19,(66)(67)(68). Previous studies have also confirmed cognitive decline over time with age and a negative association with disease duration (49,50,69,70).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown significant relationships between neuroimaging findings and cognitive impairments, including white matter track DTI measures, ventricular enlargement, gray matter and white matter atrophy, white matter lesions, increased hippocampal volume, and FDG-PET frontotemporal hypometabolism ( 4 , 9 , 12 , 19 , 66 68 ). Previous studies have also confirmed cognitive decline over time with age and a negative association with disease duration ( 49 , 50 , 69 , 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…WM lesions (WML) and WM hyperintensities (WMH) have also been reported, as well as cortical volume loss and corpus callosum atrophy 17 , 18 . In addition, WM tractography studies 18 , 19 have shown significant diffusivity alterations, including an increase in mean diffusivity (MD), axial diffusivity (AD), radial diffusivity (RD), and a decrease in fractional anisotropy (FA). The multiple alterations found in WM have prompted some authors to state that DM1 is a predominantly white matter disease 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Neuroimaging studies revealed widespread abnormalities in the brain structure of DM1 patients, particularly white-matter damage ( Minnerop et al, 2011 ; Caso et al, 2014 ; Wozniak et al, 2014 ; Baldanzi et al, 2016 ; Gourdon and Meola, 2017 ). The abnormalities of white-matter in DM1 patients manifested have increased white-matter hyperintensity load, decreased microstructural integrity, and significant diffusivity alterations ( Cabada et al, 2017 ; Lopez-Titla et al, 2021 ). These white-matter abnormalities in DM1 patients may be associated with episodic memory, executive function, and visuo-spatial impairments, which impact the quality of their life ( Meola et al, 1996 ; Modoni et al, 2008 ; Rakocevic-Stojanovic et al, 2014 ; Gallais et al, 2015 ; Schneider-Gold et al, 2015 ; Baldanzi et al, 2016 ; Okkersen et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%